(untitled) (Eurasian Medical Research Periodical, 2025)
TORCH infections pose a significant risk to pregnant women and their unborn children, with the potential for severe complications including miscarriage, stillbirth, congenital anomalies, and long-term neurological disabilities. This comprehensive overview examines the impact of Toxoplasmosis, Other (including syphilis, varicella-zoster virus, and parvovirus B19), Rubella, Cytomegalovirus (CMV), and Herpes simplex virus (HSV) infections during pregnancy. We discuss the epidemiology, transmission, clinical manifestations, diagnosis, management, and prevention strategies for TORCH infections, highlighting the importance of comprehensive prenatal care and public health interventions. Further research is needed to improve our understanding of TORCH infections and develop effective strategies for their prevention and control.